2016
DOI: 10.1021/acs.inorgchem.6b01360
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ground State Electron Configurations of High-Spin Quintet Ferrous Heme Iron in Deoxy Myoglobin Reconstituted with Trifluoromethyl Group-Substituted Heme Cofactors

Abstract: We introduced trifluoromethyl (CF) group(s) as heme side chain(s) of sperm whale myoglobin (Mb) in order to characterize the electronic nature of heme Fe(II) in deoxy Mb using F NMR spectroscopy. On the basis of the anti-Curie behavior of CF signals, we found that the deoxy Mb is in thermal equilibrium between the B, (d)(d)(d)(d)(d), and E, (d)(d)(d)(d)(d), states of the heme Fe(II), i.e., B ⇆ E. Analysis of the curvature in Curie plots has yielded for the first time ΔH and ΔS values of ∼-20 kJ mol and ∼-60 J … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 92 publications
1
4
0
Order By: Relevance
“…Furthermore, the heme Fe coordination structure of Mb­(7-PF) was almost identical to that of the wild-type protein (see Figure S1 in the Supporting Information). These findings supported the validity of the studies on the structure–function relationship of Mb through analysis of the proteins reconstituted with chemically modified hemes possessing CF 3 groups as side chains. , The presence of both Forms A and B has been revealed by the crystal structure of Mb­(7-PF). The orientation of the porphyrin moiety of 7-PF, with respect to the protein, was not greatly affected by the heme orientational disorder (Figure ).…”
Section: Resultssupporting
confidence: 71%
“…Furthermore, the heme Fe coordination structure of Mb­(7-PF) was almost identical to that of the wild-type protein (see Figure S1 in the Supporting Information). These findings supported the validity of the studies on the structure–function relationship of Mb through analysis of the proteins reconstituted with chemically modified hemes possessing CF 3 groups as side chains. , The presence of both Forms A and B has been revealed by the crystal structure of Mb­(7-PF). The orientation of the porphyrin moiety of 7-PF, with respect to the protein, was not greatly affected by the heme orientational disorder (Figure ).…”
Section: Resultssupporting
confidence: 71%
“…Molecular oxygen (O 2 ) binds reversibly to the ferrous heme Fe atom (Fe­(II)) in myoglobin (Mb). The reaction between O 2 and Fe­(II) of the deoxygenated protein (deoxy Mb) is often considered as one of the simplest biological reactions (Scheme ); however, it is much more complicated than it appears, because the reaction is formally spin forbidden. We demonstrated that the thermal equilibrium between the two different d-electron configurations of the Fe­(II) in deoxy Mb, i.e., the 5 E , (d xy )­(d xz ) 2 (d yz )­(d z 2 )­(d x 2 – y 2 ), and 5 B 2 , (d xy ) 2 (d xz )­(d yz )­(d z 2 )­(d x 2 – y 2 ), states, contributes to the acceleration of the spin-forbidden oxygenation of the protein . In addition, although the bonding of O 2 to the Fe­(II) in an end-on bent manner has been well established, the nature of the Fe–O 2 bonding in oxygenated Mb (oxy Mb) remains controversial and has been extensively debated for well over 50 years. Furthermore, the Fe­(II) of oxy Mb tends to be readily auto-oxidized into the ferric heme Fe form (Fe­(III)), and the Fe­(II) state must be maintained for reversible O 2 binding .…”
Section: Introductionmentioning
confidence: 95%
“…1−5 We demonstrated that the thermal equilibrium between the two different d-electron configurations of the Fe(II) in deoxy Mb, i.e., the 5 ), states, contributes to the acceleration of the spin-forbidden oxygenation of the protein. 6 In addition, although the bonding of O 2 to the Fe(II) in an end-on bent manner has been well established, 7−12 the nature of the Fe−O 2 bonding in oxygenated Mb (oxy Mb) remains controversial and has been extensively debated for well over 50 years. 13−17 Furthermore, the Fe(II) of oxy Mb tends to be readily autooxidized into the ferric heme Fe form (Fe(III)), and the Fe(II) state must be maintained for reversible O 2 binding.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4 To this day, aspects of this reaction remain a matter of active investigation. 5 Study of binding of dioxygen to simpler organometallic systems is important and may also provide insight into fundamental principles relevant for more complex systems. A more direct comparison between theory and experiment can be more easily made for such models since for enzymatic activation of dioxygen the ternary structure may also play a role in overall reaction energetics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Study of the binding of dioxygen to these larger and more complex bioinorganic molecules, such as Heme, dates back to a seminal paper by Pauling and co-workers in 1936 . To this day, aspects of this reaction remain a matter of active investigation …”
Section: Introductionmentioning
confidence: 99%